The interactive effects of sexual harassment and psychological capital on victims' burnout: evidence from the post-#MeToo movement era. Issue 4 (8th February 2022) - Hashmi, Syed Danial; Shahzad, Khurram; Abbas, Fakhar
Abstract : Purpose: In the post-#MeToo movement era, heightened awareness regarding harassment at workplace has forced corporations to consider gender-based harassment as a serious issue. This study aims to theorise and test psychological capital as a resource reservoir to cope with burnout experienced in the form of emotional exhaustion, depersonalisation and reduced personal accomplishments as results of gender-based harassment at workplace. Design/methodology/approach: Multi-wave data were collected from 304 female employees working in project-based organisations in the information technology industry in Pakistan. Findings: The analysis shows contradictory findings about the prevalence of sexual harassment when a behavioural measurement approach was used against a direct query method. The results also show that gender harassment leads to burnout causing emotional exhaustion, depersonalisation and reduced personal accomplishment among the victims. However, psychological capital helps victims cope with these adverse effects of gender harassment. Practical implications: Managers need to boost the psychological capital of female workers and devise effective policies to combat gender harassment in the workplace. Enforcement of legislation regarding harassment in the workplace should be ensured, which will also indicate seriousness towards the achievement of the United Nations' Sustainable Development Goal No. 5, that is, gender equality. Originality/value: To the best of the authors' knowledge, this study is the first to present psychological capital as a resource reservoir to combat the negative effects of gender harassment and has been conducted in less studied non-Western work settings.